Stress-assisted annealing method and application of HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates

CN122952863APending Publication Date: 2026-10-20MOZI LABORATORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077302.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,这一高温要求与现有柔性衬底的低耐受温度形成了根本性矛盾

Benefits of technology

(1)本发明采用超薄柔性玻璃作为衬底,兼具优异的柔韧性(可耐受反复的小半径弯折)和高温耐受性(可兼容高达550℃的退火工艺),克服了传统有机聚合物衬底无法承受高温退火、云母衬底可扩展性差的缺陷,为在柔性衬底上直接制备高质量HfO2基铁电薄膜提供了理想的衬底平台。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of ferroelectric materials technology, and particularly to a stress-assisted annealing method and application for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates. The method includes the following steps: sequentially depositing a bottom electrode, an HfO2-based ferroelectric thin film, and a top electrode on an ultrathin flexible glass substrate to obtain a stacked structure; fixing the stacked structure onto a bending jig to subject it to bending strain, and then performing rapid annealing; after annealing, cooling the bending jig with the stacked structure to room temperature, and then releasing the stacked structure from the bending jig to obtain the HfO2-based ferroelectric thin film based on the ultrathin flexible glass substrate. This invention overcomes the limitations of high-temperature annealing by using ultrathin flexible glass as the substrate and actively applying bending stress during annealing to control crystallization behavior, thereby achieving the direct fabrication of high-performance HfO2-based ferroelectric thin films on flexible substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ferroelectric materials technology, and in particular to a stress-assisted annealing method and application for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates. Background Technology

[0002] With Hf 0.5 Zr 0.5 HfO2-based ferroelectric thin films, represented by O2 (HZO), have shown broad application prospects in fields such as non-volatile memory, negative capacitance transistors, and neuromorphic computing due to their excellent ferroelectric properties, good thickness miniaturization capabilities, and high compatibility with CMOS (Complementary Metal-Oxide-Semiconductor) processes. With the rapid development of flexible electronics technology, integrating HfO2-based ferroelectric thin films onto flexible substrates to realize bendable and wearable flexible ferroelectric devices has become an important development direction in this field.

[0003] The ferroelectricity of HfO2-based ferroelectric thin films originates from the metastable orthorhombic phase (Pca21). The formation of this phase is extremely sensitive to the annealing process, typically requiring rapid thermal annealing at temperatures above 400°C to induce sufficient crystallization. However, this high-temperature requirement fundamentally contradicts the low temperature tolerance of existing flexible substrates. Specifically, while traditional organic polymer substrates (such as polyimide (PI) and polyester (PET)) possess good flexibility, their temperature tolerance is generally below 350°C, making them unable to withstand the high-temperature annealing conditions required for HfO2-based ferroelectric thin films. This results in poor film crystallinity, low orthorhombic phase content, and severe degradation of remanent polarization. Mica substrates, although capable of withstanding higher temperatures, suffer from poor scalability and are prone to delamination along cleavage planes, making them unsuitable for practical applications. Therefore, finding a substrate material that combines excellent flexibility and high-temperature tolerance, and developing a suitable annealing process, has become a key technical challenge for achieving high-performance flexible HfO2-based ferroelectric thin films. Summary of the Invention

[0004] The purpose of this invention is to provide a stress-assisted annealing method and application for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates. By selecting ultrathin flexible glass as the substrate to overcome the limitations of high-temperature annealing, and actively applying bending stress during the annealing process to control the crystallization behavior, high-performance HfO2-based ferroelectric thin films can be directly prepared on flexible substrates.

[0005] To achieve the above objectives, this invention provides a stress-assisted annealing method for HfO2-based ferroelectric thin films on ultrathin flexible glass substrates, comprising the following steps: S1. A bottom electrode, an HfO2-based ferroelectric thin film, and a top electrode are sequentially deposited on an ultrathin flexible glass substrate to obtain a stacked structure. S2. Fix the laminated structure onto the bending fixture to subject it to bending strain, and then perform rapid annealing. S3. After annealing, the bending fixture with the stacked structure is cooled to room temperature, and then the stacked structure is released from the bending fixture to obtain an HfO2-based ferroelectric thin film based on an ultrathin flexible glass substrate.

[0006] Preferably, in S1, the ultrathin flexible glass substrate is selected from one of high-alumina glass, soda-lime glass, and low-alkali glass, and the thickness of the ultrathin flexible glass substrate is 20-100μm.

[0007] Preferably, in S1, the HfO2-based ferroelectric thin film is a ferroelectric HfO2-based ferroelectric thin film doped with modifying elements, including one or more of Si, Zr, Al, Y, La, Ce, Sr, and Gd.

[0008] Preferably, in S1, the materials of both the bottom electrode and the top electrode are selected from one of TiN, W, Mo, Ni, Pt, TaN, and poly-Si.

[0009] Preferably, in S1, the deposition methods for the bottom electrode, the HfO2-based ferroelectric thin film, and the top electrode are all selected from atomic layer deposition, magnetron sputtering, and pulsed laser deposition.

[0010] Preferably, in S2, the radius of curvature of the bending fixture is in the range of 1-50mm.

[0011] Preferably, in S2, the bending strain state is tensile strain, which is achieved by fixing the laminated structure to the convex surface of the bending fixture.

[0012] Preferably, in S2, the rapid annealing annealing temperature is 350℃-550℃, the annealing time is 20s-300s, and the annealing atmosphere is nitrogen.

[0013] This invention also provides applications of HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates. The HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates prepared by the stress-assisted annealing method described above can be used to prepare flexible non-volatile memories, flexible wearable electronic devices, or flexible sensors.

[0014] Mechanism of the invention: This invention utilizes the characteristic of ultrathin flexible glass substrates to maintain stable elastic strain under bending conditions. During annealing, a controllable tensile strain is actively applied to the stacked structure using a bending fixture. This external mechanical stress is transferred to the interior of the HfO2-based ferroelectric thin film, altering the nucleation barrier of the orthorhombic phase (Pca21) and reducing the free energy for orthorhombic phase formation. This induces preferential grain growth along a favorable orientation during thermal annealing. Simultaneously, the stress field affects the migration and distribution of oxygen vacancies within the film, further stabilizing the orthorhombic phase structure. The synergistic effect of the stress and temperature fields allows for higher orthorhombic phase content and superior ferroelectric properties under the same thermal budget.

[0015] Therefore, the stress-assisted annealing method and application of HfO2-based ferroelectric thin films on ultrathin flexible glass substrates in this invention have the following beneficial effects: (1) The present invention uses ultrathin flexible glass as a substrate, which has both excellent flexibility (can withstand repeated small-radius bending) and high temperature resistance (can be compatible with annealing processes up to 550°C), overcoming the defects of traditional organic polymer substrates that cannot withstand high-temperature annealing and mica substrates that have poor scalability, and providing an ideal substrate platform for the direct preparation of high-quality HfO2-based ferroelectric thin films on flexible substrates.

[0016] (2) In the annealing process, the present invention actively introduces bending stress and uses the synergistic effect of stress field and thermal field to regulate the crystallization behavior of HfO2-based ferroelectric thin film. Compared with traditional stress-free annealing, this method changes the nucleation barrier of orthorhombic phase by external stress, induces preferential orientation growth of grains, and affects the migration and distribution of oxygen vacancies. It can significantly improve the orthorhombic phase content and residual polarization intensity of HfO2-based ferroelectric thin film without increasing the thermal budget.

[0017] (3) This invention combines an ultrathin flexible glass substrate with a bending stress-assisted annealing process, which solves the problem of poor crystal quality of HfO2-based ferroelectric thin films on flexible substrates, and provides a new process route for the direct preparation of high-performance HfO2-based ferroelectric thin films on flexible substrates. The flexible ferroelectric thin films and devices prepared based on this method can achieve ferroelectric properties close to or even exceeding those of thin films prepared on rigid substrates while maintaining excellent flexibility.

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the HfO2-based ferroelectric thin film stacked structure and its bending stress state based on an ultrathin flexible glass substrate according to the present invention. Figure 2 This is a schematic flowchart of the stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to the present invention. Detailed Implementation

[0020] This invention provides a stress-assisted annealing method for HfO2-based ferroelectric thin films on ultrathin flexible glass substrates, comprising the following steps: S1. A bottom electrode, an HfO2-based ferroelectric thin film, and a top electrode are sequentially deposited on an ultrathin flexible glass substrate to obtain a stacked structure. S2. Fix the laminated structure onto the bending fixture to subject it to bending strain, and then perform rapid annealing. S3. After annealing, the bending fixture with the stacked structure is cooled to room temperature, and then the stacked structure is released from the bending fixture to obtain an HfO2-based ferroelectric thin film based on an ultrathin flexible glass substrate.

[0021] In this invention, ultrathin flexible glass refers to a special glass material with a thickness of less than 100μm, which, while maintaining the high light transmittance, high hardness, and high stability of glass, achieves the characteristics of repeated bending and rolling.

[0022] In this invention, stress-assisted annealing refers to actively applying and maintaining a certain external mechanical stress during the annealing and crystallization process of HfO2-based ferroelectric thin films. By utilizing the coupling effect of the stress field and the temperature field, the phase transition behavior, microstructure, and defect distribution of the thin film can be controlled.

[0023] Preferably, in S1, the ultrathin flexible glass substrate is selected from one of high-alumina glass, soda-lime glass, and low-alkali glass, and the thickness of the ultrathin flexible glass substrate is 20-100μm.

[0024] The ultrathin flexible glass substrate of the present invention can withstand an annealing temperature of not less than 600°C.

[0025] Preferably, in S1, the HfO2-based ferroelectric thin film is a ferroelectric HfO2-based ferroelectric thin film doped with modifying elements, including one or more of Si, Zr, Al, Y, La, Ce, Sr, and Gd.

[0026] Preferably, in S1, the materials of the bottom electrode and the top electrode are both selected from TiN, W, Mo, Ni, Pt, TaN, and poly-Si (polycrystalline silicon).

[0027] Preferably, in S1, the deposition methods for the bottom electrode, the HfO2-based ferroelectric thin film, and the top electrode are all selected from atomic layer deposition, magnetron sputtering, and pulsed laser deposition.

[0028] The preparation of precursors for depositing bottom electrodes, HfO2-based ferroelectric thin films, and top electrodes is a prior art, and this invention does not further limit it.

[0029] Preferably, in S2, the radius of curvature of the bending fixture is in the range of 1-50mm.

[0030] Preferably, in S2, the bending strain state is tensile strain, which is achieved by fixing the laminated structure to the convex surface of the bending fixture. Conventional annealing methods typically use metal electrodes with a smaller coefficient of thermal expansion than HfO2-based ferroelectric thin films to provide tensile stress. The greater the difference in coefficients of thermal expansion, the stronger the stress and the better the crystallinity of the orthorhombic phase (ferroelectric phase). However, this method is limited to tungsten electrodes.

[0031] By adjusting the bending curvature, this invention can provide the crystallization stress required for HfO2-based ferroelectric thin films, regardless of the type of electrode.

[0032] Preferably, in S2, the rapid annealing temperature is 350℃-550℃, the annealing time is 20s-300s, and the annealing atmosphere is nitrogen. The nitrogen atmosphere mainly serves a protective function, preventing oxidation or damage to the HfO2-based ferroelectric thin film or metal electrode at high temperatures, and ensuring the chemical stability of the film composition and electrode interface.

[0033] The annealing temperature is controlled within the above range. On the one hand, it provides the necessary thermal activation energy for the transformation of HfO2-based ferroelectric thin films from amorphous or initial crystalline state to ferroelectric orthorhombic phase, enabling atoms to obtain sufficient mobility to complete lattice reconstruction. On the other hand, it avoids the orthorhombic phase from transforming into the high-temperature stable tetragonal or monoclinic phase due to excessively high temperature, thereby ensuring the content of effective ferroelectric orthorhombic phase in the thin film.

[0034] Controlling the annealing time within the above range can achieve a balance between sufficient crystallization and defect control. If the annealing time is too short, atomic migration and lattice rearrangement will be insufficient, orthorhombic phase crystallization will be incomplete, and the ferroelectric properties of the thin film will not be fully utilized. If the annealing time is too long, it will easily lead to excessive proliferation and aggregation of oxygen vacancies inside the thin film, forming defect complexes or leakage channels, resulting in degradation of ferroelectric properties and deterioration of film durability.

[0035] This invention also provides applications of HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates. The HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates prepared by the stress-assisted annealing method described above can be used to prepare flexible non-volatile memories, flexible wearable electronic devices, or flexible sensors.

[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0037] Example 1 like Figures 1 to 2As shown, this invention provides a stress-assisted annealing method for HfO2-based ferroelectric thin films on ultrathin flexible glass substrates, comprising the following steps: S1. The 50μm thick ultrathin flexible glass (high-alumina glass) substrate is cleaned and dried. A 30nm TiN bottom electrode and a 10nm Hf electrode are then deposited on the substrate using plasma-enhanced atomic layer deposition (PEALD). 0.5 Zr 0.5 An O2 ferroelectric thin film and a 30nm TiN top electrode were fabricated, and the electrode patterning was achieved to obtain a stacked structure.

[0038] S2. Fix the laminated structure onto a convex bending fixture with a radius of curvature of 20 mm, placing the laminated structure in a state of tensile strain. The laminated structure is fixed by pressure plates at both ends of the fixture, ensuring that the film surface is uniformly attached to the curved surface of the fixture. Then, place the bending fixture with the laminated structure fixed in it into a rapid thermal annealing furnace and anneal at 500°C for 60 seconds under a nitrogen atmosphere. Throughout the annealing process, the sample remains in a state of bending strain.

[0039] S3. After annealing, the bending fixture with the stacked structure is cooled to room temperature, and then the stacked structure is released from the bending fixture to obtain an HfO2-based ferroelectric thin film based on an ultrathin flexible glass substrate.

[0040] Example 2 The difference from Example 1 is that a convex bending fixture with a radius of curvature of 10mm is used in S2 to put the laminated structure in a strong tensile strain state. All other aspects are the same as in Example 1.

[0041] Comparative Example 1 The difference from Example 1 is that in S2, the laminated structure is fixed on a flat fixture and subjected to rapid hot annealing without applying bending stress. The annealing temperature is 500°C. All other aspects are the same as in Example 1.

[0042] Comparative Example 2 The difference from Example 1 is that a mica substrate is used instead of an ultrathin flexible glass substrate in S1, while the rest is the same as in Example 1.

[0043] Comparative Example 3 The difference from Example 1 is that in S1, a polyimide (PI) substrate is used instead of an ultrathin flexible glass substrate, while the rest is the same as in Example 1.

[0044] Comparative Example 4 The difference from Example 1 is that the annealing temperature in S2 is 600°C, while the rest is the same as in Example 1.

[0045] The performance of the HfO2-based ferroelectric thin films of Examples 1-2 and Comparative Examples 1-4 was tested. The test results are shown in Table 1-2. The test methods are as follows: Ferroelectric orthorhombic phase content: determined by the Rietveld refinement method of X-ray diffraction; Residual polarization intensity: measured using a TF Analyzer 3000 ferroelectric analyzer at a test frequency of 1 kHz; Thin film durability: The fatigue test mode was adopted, the test frequency was 1MHz, and the electric field amplitude was 3MV / cm; Dynamic bending reliability: A dynamic bending test system is used, with a bending radius of 5mm and a bending frequency of 1Hz.

[0046] Table 1 Performance data of Examples 1-2 and Comparative Examples 1 and 4

[0047] As shown in Table 1, the orthorhombic phase content and remanent polarization intensity of Examples 1-2 after bending stress-assisted annealing are significantly better than those of Comparative Example 1. This indicates that the introduction of bending stress significantly promotes the transformation of HfO2-based ferroelectric thin films from non-ferroelectric phases (such as monoclinic or tetragonal phases) to ferroelectric orthorhombic phases (Pca21). Essentially, the external mechanical stress lowers the nucleation barrier of the orthorhombic phase, providing additional nucleation driving force for the grains, thereby achieving a higher orthorhombic phase content and stronger ferroelectric response under the same thermal budget conditions. The durability of Examples 1-2 is also better than that of Comparative Example 1, indicating that while bending stress-assisted annealing improves ferroelectric performance, it does not introduce an additional fatigue degradation mechanism. Instead, it enhances the durability of the film to some extent by optimizing crystal quality and reducing defect density. Furthermore, the durability of Examples 1-2 is significantly better than that of Comparative Example 4. This is because while higher annealing temperatures can promote crystallization, they often also form more defects inside the film, leading to increased leakage current and decreased durability.

[0048] Table 2 Performance data of Example 1 and Comparative Examples 2-3

[0049] As shown in Table 2, although the mica substrate in Comparative Example 2 can withstand an annealing temperature of 500℃, during the annealing process, due to the combined effects of thermal and mechanical stress, the substrate undergoes delamination and cracking along the cleavage plane, resulting in the destruction of the structural integrity of the HfO2-based ferroelectric thin film and making it impossible to complete the ferroelectric performance test. Even under cold bending conditions without annealing, the minimum bending radius of the mica substrate is approximately 5mm, and the number of bends it can withstand does not exceed 20,000, which is far from meeting the actual usage requirements of flexible electronic devices for reliability under repeated bending.

[0050] In Comparative Example 3, the polyimide substrate exhibited severe yellowing and thermal shrinkage under annealing at 500°C, resulting in loss of substrate dimensional stability. The HfO2-based ferroelectric thin film failed to form a continuous and dense crystalline layer due to substrate deformation, and the ferroelectric orthorhombic phase failed to form effectively. Even under optimized low-temperature annealing conditions, its tolerance temperature could not exceed 350°C, fundamentally contradicting the crystallization temperature required for HfO2-based ferroelectric thin films.

[0051] In contrast, the ultrathin flexible glass substrate used in Example 1 remained intact after annealing at 500°C and could withstand a bending radius of 5 mm with a strength of not less than 1 × 10⁻⁶. 6 The ultrathin flexible glass substrate exhibits no performance degradation during dynamic bending. Compared to mica and polyimide substrates, the bending reliability of the ultrathin flexible glass substrate is improved by more than 50 times and 5 times, respectively, fully demonstrating its significant advantages as a substrate for flexible ferroelectric devices.

[0052] Therefore, the present invention adopts the stress-assisted annealing method and application of HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates, which has long been a core problem faced by HfO2-based ferroelectric thin films on flexible substrates, such as the incompatibility between high-temperature annealing and substrate flexibility, poor crystal quality, and deterioration of ferroelectric performance, and provides a solid technical foundation for the practical development of high-performance flexible ferroelectric devices.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A stress-assisted annealing method for HfO2-based ferroelectric thin films on ultrathin flexible glass substrates, characterized in that: Includes the following steps: S1. A bottom electrode, an HfO2-based ferroelectric thin film, and a top electrode are sequentially deposited on an ultrathin flexible glass substrate to obtain a stacked structure. S2. Fix the laminated structure onto the bending fixture to subject it to bending strain, and then perform rapid annealing. S3. After annealing, the bending fixture with the stacked structure is cooled to room temperature, and then the stacked structure is released from the bending fixture to obtain an HfO2-based ferroelectric thin film based on an ultrathin flexible glass substrate.

2. The stress-assisted annealing method for HfO2-based ferroelectric thin films on ultrathin flexible glass substrates according to claim 1, characterized in that: In S1, the ultrathin flexible glass substrate is selected from one of high-alumina glass, soda-lime glass, and low-alkali glass, and the thickness of the ultrathin flexible glass substrate is 20-100μm.

3. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S1, the HfO2-based ferroelectric thin film is a ferroelectric HfO2-based ferroelectric thin film doped with modifying elements, including one or more of Si, Zr, Al, Y, La, Ce, Sr, and Gd.

4. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S1, the materials of both the bottom electrode and the top electrode are selected from one of TiN, W, Mo, Ni, Pt, TaN, and poly-Si.

5. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S1, the deposition methods for the bottom electrode, the HfO2-based ferroelectric thin film, and the top electrode are all selected from atomic layer deposition, magnetron sputtering, and pulsed laser deposition.

6. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S2, the radius of curvature of the bending fixture ranges from 1 to 50 mm.

7. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S2, the bending strain state is tensile strain, which is achieved by fixing the laminated structure to the convex surface of the bending fixture.

8. The stress-assisted annealing method for HfO2-based ferroelectric thin films based on ultrathin flexible glass substrates according to claim 1, characterized in that: In S2, the rapid annealing annealing temperature is 350℃-550℃, the annealing time is 20s-300s, and the annealing atmosphere is nitrogen.

9. The application of HfO2-based ferroelectric thin films on ultrathin flexible glass substrates, characterized in that: The HfO2-based ferroelectric thin film based on an ultrathin flexible glass substrate, prepared by the stress-assisted annealing method according to any one of claims 1-8, can be used to prepare flexible non-volatile memory, flexible wearable electronic devices, or flexible sensors.